On network coding in wireless cooperative and cognitive communications - Li, Qiang (2011)
Network coding, first proposed in the seminal work by Ahlswede, Cai, Li, and Yeung, has attracted significant interest in the last decade in both academia and the industry due to its versatility and promising potential in improving the performance of communication networks. In contrast to conventional routing architecture which is typical in most computer networks where intermediate nodes of a network can only store-and-forward the received packets, the intermediate nodes are allowed to perform random mapping of the received packets in network coding. With independent information flows intended for different receivers combining at the intermediate nodes, the bottleneck of data communications has shifted from point-to-point links to the whole network topology. Although network coding was originally designed for wireline networks with error-free links, wireless networks provide a fertile ground for various applications based on network coding.